Decision making tools for resource allocation based on Maqasid Al- Shariah - Moussa, Larbani; Mustafa Omar, Mohammed (Islamic Research and Training Institute (IRTI), Islamic Development Bank, 2011)
The major focus of past literature on Al-Maqasid was on developing the theory, and most of the discussion centered on its legal dimensions. The pioneering works emanated from scholars such as, Al-Juwayni (n.d), Al-Ghazali (1901), Al-Shatibi (n.d), Ibn ‘Ashur (1998) and Ibn Taymiyyah (al-Raysuni, 1992). Recently, the application of Al-Maqasid in various disciplines including economics and finance has been gaining prominence. Among the leading economists who have written on the subject, to mention a few are Chapra (1985; 2004), Biraima M.E. (1991), Siddiqi (2000), Ahmad (2000), Atya (2003), Hasan (2004) and Al-Najjar (2008). Their works however, relate Al-Maqasid to the discipline of economics in a broad theoretical framework. Dusuki (2005) went a step further relating Al-Maqasid to Corporate Social Responsibility. Hameed et al. (2005) tried to develop what they termed as ‘Islamicity Disclosure Index’ to measure and compare the performances of two Islamic banks. A refined work by Mustafa et al. (2008) developed a quantitative performance measure for Islamic banking from the theory of Al-Maqasid. The present study is taking Al-Maqasid a step further. It develops a decision making tool based on Al-Maqasid al-Shari[ah and their levels of Maslahah for the managers of firms to use in allocating their investible resources to vital sectors of the economy. The developed model can be extended to other decision making problems. Thus, this contribution opens a new direction of research: the analytic operationalization of Al-Maqasid al-Shari'ah.